An Instantaneous Frequency Identification Algorithm for Time-Varying Frequency Signals - Li Xiaocong; Meng Xuanren (IEEE Access, 2019)
A high-precision instantaneous frequency (IF) identification algorithm is proposed in this paper. The algorithm is based on the relationship between the signal phase and time, and uses Taylor's expansion to parameterize the time-varying frequency. It can accurately identify the IF of various frequency-modulated (FM) signals. The simulation results show that high identification precision can be obtained when the frequency of the signal is stable or modulated by linear and nonlinear functions. Compared to the conventional IF identification algorithms Hilbert transform (HT) and Wigner-Ville distribution (WVD), the proposed algorithm performs better in accuracy. Besides, the proposed algorithm is not sensitive to the amplitude-modulation behavior, and it shows better precision than the Direct Quadrature (DQ) algorithm, which is an IF identification algorithm of the amplitude-modulated signal. The calculation amount of the proposed algorithm is not related to the sampling rate. Increasing the sampling rate can make the identification precision higher without changing the calculation speed. It can provide the theoretical basis for the IF identification of a grid-connected inverter and other automatic devices in the power system.